The Values of Islamic Education in Pappasêng of the Bugis Tribe and Its Implementation in Elementary School Learning - Ramadan, Syahru (DIDAKTIKA, 2025)
Pappasêng is one of the oral literature of the Bugis tribe in the form of traditional expressions or admonitions that are often conveyed by parents (to riyolo) to the next generation (to ri munri). The advice contains advice to be used as a guideline in living life. Pappasêng is still firmly held by the Bugis people, especially the people in Cina District, Bone Regency. They state that the values in Pappasêng remain relevant to today's life. The purpose of this research is to describe the value of Islamic character in Pappasêng who lives in the Cina sub-district community. This research is a qualitative descriptive research with a naturalistic approach. The data in the study are Pappasêng's expressions from the sources and the documentation studies that support the research. The results of this study show that Pappasêng's expression is in line with Islamic teachings. The expression Pappasêng contains several Islamic character values, namely monotheism, honesty, hard work, firm stance (istiqamah), good prejudice (husnuzan), compassion, and cleverness. These values should be instilled in the next generation by maintaining Pappasêng and continuing to pass it on, including in elementary school learning. This can be done by making pappasêng as a learning material for local languages, inserting pappasêng when giving advice or stories to students, and using pappasêng in explaining other learning materials.